Comparative study on the feed utilisation of local and cross bred cows - Chacko C T (Department of Animal Husbandary, College of Veterinary and Animal Sciences, 1975)
A comparison of the feed utilisation efficiency between Sindhi and Sindhi x Jersey cross bred lactating cows of the University livestock farm was made. Six cows each from the two groups were paired on the basis of the lactation number and stage of lactation. The animals were stall fed for 76 days including a pre – trial period of 15 days. The ration consisted of a concentrate feed and guinea grass to meet the protein requirement and paddy straw ad libitum. The following observations were recorded for individual cows: i) daily intake of different food ingredients; ii) daily milk yield ; iii) daily out put of dung; iv) body weight and body measurements during the pre – trial period, commencement, middle and close of the experiment; v) percentage of butter fat and total solids of individual composite samples tested once in a week; and vi) calculation of gross efficiency of feed utilisation. The following inference could be drawn: 1. The total dry matter consumption by the Sindhi and the cross bred cows were 3.30 kg and 3.61 kg per 100 kg body weight respectively and the dry matter consumption from roughage alone was 2.04 kg and 2.10 kg respectively. 2. The digestibility coefficients of dry matter, crude protein and nitrogen free extract were higher for the cross breds and in straight breds it was higher for crude fibre. For ether extract the digestibility coefficient was the same in both the groups. 3. The straight bred cows gained weight and increased in heart girth significantly (P < 0.01) during the experimental period, but no significant weight gain was recorded in cross breds. The increase in heart girth was significant (P < 0.05) among cross breds. The height at withers and body length did not increase significantly in the two groups. 4. The average daily 4% fat corrected milk yields were significantly higher (P < 0.01) in the cross breds. No significant difference was noticed between the two groups in the percentages of fat and total solids in milk. 5. The average gross efficiency of feed utilisation for milk production was 24.65 in cross breds and it was 18.62 in straight breds indicating that the cross breds were superior to the straight bred in the utilisation of feeds for milk production.